2000
DOI: 10.1111/j.1467-842x.2000.tb01591.x
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of a ‘cluster’ of hepatitis B in teenagers from an Indigenous community in North Queensland

Abstract: Initiatives to control hepatitis B need to be enhanced within existing maternal and child health, sexual health, alcohol and drug and chronic disease management programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…The highest HBsAg prevalence (26%) was reported by two studies; one was a cross sectional survey by Burrell and colleagues in 1979-82 of stored blood samples [31] and the other an investigation of a cluster of HBsAg seropositive cases in northern Queensland among Indigenous adolescents [39]. There were six studies in adults and pregnant women; three were community-based surveys, and three serology testing of a convenient sample of stored blood specimens.…”
Section: Resultsmentioning
confidence: 99%
“…The highest HBsAg prevalence (26%) was reported by two studies; one was a cross sectional survey by Burrell and colleagues in 1979-82 of stored blood samples [31] and the other an investigation of a cluster of HBsAg seropositive cases in northern Queensland among Indigenous adolescents [39]. There were six studies in adults and pregnant women; three were community-based surveys, and three serology testing of a convenient sample of stored blood specimens.…”
Section: Resultsmentioning
confidence: 99%
“…All our isolates are HBsAg serotype ayw3 based on aa sequence at positions 122, 127, and 160. Concerns have been raised regarding the efficacy of hepatitis B vaccine in Indigenous Australians that is derived from serotype adw virus. There is also some evidence to raise concerns about HBV vaccine efficacy in the Gambia where there is also a mismatch between vaccine (serotype adw) and endemic HBV that is genotype A‐2, serotype ayw‐4 .…”
Section: Discussionmentioning
confidence: 99%
“…In Australia, the overall prevalence of HBV is estimated to be low (0.8–0.9%) . However, HBV is endemic in Indigenous communities in the Northern Territory (NT) of Australia, with estimates of HBV seroprevalence ranging from 5% to 20% . The predominant route of transmission in this setting is likely to be perinatal.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of hepatitis B virus (HBV) infection has not been comprehensively defined in Australia, although a national serosurvey in 1999 estimated 0.49–0.87% of the population were infected 1 (HBV surface antigen (HBsAg)‐positive). HBV infection appears more prevalent in Aboriginal Australians than others, with serological evidence of past infection (HBV core antibody (HBcAb)‐positive and HBsAg‐negative) found in 30–90% 1–4 . Antenatal seroprevalence studies in the Northern Territory (NT) found a current infection prevalence of 3.7%–5.5% 5,6 .…”
Section: Documented Hbv Serology In 112 Patients Who Had An Adult Heamentioning
confidence: 99%